2015
DOI: 10.1165/rcmb.2014-0142oc
|View full text |Cite
|
Sign up to set email alerts
|

Wood Smoke Enhances Cigarette Smoke–Induced Inflammation by Inducing the Aryl Hydrocarbon Receptor Repressor in Airway Epithelial Cells

Abstract: Our previous studies showed that cigarette smokers who are exposed to wood smoke (WS) are at an increased risk for chronic bronchitis and reduced lung function. The present study was undertaken to determine the mechanisms for WS-induced adverse effects. We studied the effect of WS exposure using four cohorts of mice. C57Bl/6 mice were exposed for 4 or 12 weeks to filtered air, to 10 mg/m 3 WS for 2 h/d, to 250 mg/m 3 cigarette smoke (CS) for 6 h/d, or to CS followed by WS (CW). Inflammation was absent in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 56 publications
(58 reference statements)
3
38
0
2
Order By: Relevance
“…Previous studies indicate that AHRR is transcriptionally up-regulated by activation of the Ah Receptor pathway 12, 13 . Interestingly, RRBS showed that the AHRR cg05575921 locus is located in a smoking-associated DMR, which appears to overlap an intragenic enhancer that is activated, accompanied by up-regulation of AHRR expression, when monocytes differentiate into macrophages 19 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies indicate that AHRR is transcriptionally up-regulated by activation of the Ah Receptor pathway 12, 13 . Interestingly, RRBS showed that the AHRR cg05575921 locus is located in a smoking-associated DMR, which appears to overlap an intragenic enhancer that is activated, accompanied by up-regulation of AHRR expression, when monocytes differentiate into macrophages 19 .…”
Section: Discussionmentioning
confidence: 97%
“…The consequences of AHRR up-regulation in monocytes is unclear, but given the potential role of AHRR in macrophage biology 19 and suppression of anti-inflammation 13 , up-regulation of AHRR could plausibly alter the function of monocytes and macrophages in smokers. While there is currently no known role for AHRR in atherogenesis, a number of studies have shown that activation of the Ah Receptor pathway promotes atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Благодаря исследованиям ассоциаций эпигенома (EWAS -Epigenome-wide Association Studies) уже выявле-но большое количество CpG сайтов (CpG) в различных генах, метилирование которых связано с курением [15][16][17][18][19][20][21][22][23][24][25][26][27]. Все они вовлечены в разнообразные клеточные про-цессы, например AHRR и CYP1A1 участвуют в сигнальном ПРОФИЛАКТИЧЕСКАЯ МЕДИЦИНА, 6,2015 Сведения об авторах: Киселева Анна Витальевна -к.б.н., н.с.…”
unclassified